2014
DOI: 10.1007/978-94-017-8890-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Interactions in the Rhizosphere

Abstract: Production of plant biomass is one of the main ecosystem services delivered by soil. The area closely surrounding the root surface, the rhizosphere, is where plants interact with soil organisms. The interaction of a plant with soil microorganisms may result in several benefi ts to the plant, including improved nutrient availability or uptake, protection against pests and pathogens, improved tolerance to abiotic stress and growth promotion via hormones. Those relationships between plant and microorganisms deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 142 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…Beta-and Gamma-Proteobacteria were more abundant in the rhizosphere of the P-fertilized plants. Both classes are known to play a key role in rhizosphere colonization (Inceoglu et al, 2010;Hol et al, 2014) and are relatively fastgrowing copiotrophic microbes (Philippot et al, 2013). The control treatment showed a higher abundance of Actinobacteria and especially Firmicutes than the P-fertilization treatment, which are also known to colonize the rhizosphere (DeAngelis et al, 2009;Eastman et al, 2014;Haesler et al, 2014;Hol et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Beta-and Gamma-Proteobacteria were more abundant in the rhizosphere of the P-fertilized plants. Both classes are known to play a key role in rhizosphere colonization (Inceoglu et al, 2010;Hol et al, 2014) and are relatively fastgrowing copiotrophic microbes (Philippot et al, 2013). The control treatment showed a higher abundance of Actinobacteria and especially Firmicutes than the P-fertilization treatment, which are also known to colonize the rhizosphere (DeAngelis et al, 2009;Eastman et al, 2014;Haesler et al, 2014;Hol et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…We can only speculate about the mechanism behind this positive association. Microorganisms in general can help the plant with nutrient uptake, induce production of secondary metabolites, produce hormones that affect plant growth ( Hol et al, 2014 ), all of those could change hyperspectral reflectance patterns (e.g., Kumar et al, 2001 ; Ayala-Silva and Beyl, 2005 ; Ferwerda et al, 2005 ; Font et al, 2005 ; Carvalho et al, 2013a ). Soil biodiversity might benefit plants directly via changes in nutrient availability, or indirectly by offering protection against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Live soil contains a variety of organisms, large ones like earthworms, ants, and larvae and microbial ones like protozoa, bacteria, and fungi. Some of those organisms will affect plant chemical composition, either by mutualistic effects such as providing nutrients, producing growth hormones, suppressing diseases ( Hol et al, 2014 ) or by pathogenic interactions, which damage plant tissue and could trigger the plants’ defense system ( Termorshuizen, 2014 ). Variation in the plant’s chemical composition can be detected by high-resolution spectroscopy ( Asner and Martin, 2008 ; Ramoelo et al, 2012 ; Carvalho et al, 2013a , b ; Kokaly and Skidmore, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 244 reduced bacterial abundance found in adelgid-infested hemlock stands may simultaneously be 245 linked to reduced ectomycorrhizal associations and changes in root and soil nutrient chemistry 246 associated with infestation. Indeed, some studies have found that soil communities experiencing 247 mycorrhizal loss also lose their fungally-associated bacteria (Hol et al, 2014). However, the 248 significant decline in absolute numbers of bacteria suggests resource limitation from the root.…”
Section: ) 243mentioning
confidence: 99%